The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1261/rna.444007
|View full text |Cite
|
Sign up to set email alerts
|

The NS3 protein of Rice hoja blanca tenuivirus suppresses RNA silencing in plant and insect hosts by efficiently binding both siRNAs and miRNAs

Abstract: RNA silencing plays a key role in antiviral defense as well as in developmental processes in plants and insects. Negative strand RNA viruses such as the plant virus Rice hoja blanca tenuivirus (RHBV) replicate in plants and in their insect transmission vector. Like most plant-infecting viruses, RHBV encodes an RNA silencing suppressor, the NS3 protein, and here it is demonstrated that this protein is capable of suppressing RNA silencing in both plants and insect cells. Biochemical analyses showed that NS3 effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
79
0
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3
3

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(87 citation statements)
references
References 57 publications
5
79
0
3
Order By: Relevance
“…(Csorba et al 2007;Harries et al 2008;Hemmes et al 2007;Kubota et al 2003;Lakatos et al 2006;Merai et al 2005Merai et al , 2006Silhavy et al 2002). Amongst these, probably the best known is the tombusviral p19 protein .…”
Section: Vsirna Sequestrationmentioning
confidence: 99%
“…(Csorba et al 2007;Harries et al 2008;Hemmes et al 2007;Kubota et al 2003;Lakatos et al 2006;Merai et al 2005Merai et al , 2006Silhavy et al 2002). Amongst these, probably the best known is the tombusviral p19 protein .…”
Section: Vsirna Sequestrationmentioning
confidence: 99%
“…In addition to interfere with IFN signaling pathway, viruses in general (Hemmes et al, 2007) and HCV in particular are able to interfere with RNAi-dependent antiviral effect. Using cell lines that express constitutively green fluorescent protein (GFP) and in which HCV protein expression is inducible, Ji et al demonstrated that silencing of GFP gene by siRNA was inhibited in the presence of the full length HCV polyprotein ; HCV E2 protein was shown to be responsible for this inhibition (Ji et al, 2008).…”
Section: Interferon Signaling Pathway and Viral Resistancementioning
confidence: 99%
“…RHBV is transmitted by insect vector and observed to be having life cycles in both plants and insects. RHBV nonstructural protein NS3, encoded by RNA3, has been reported to be an RNA silencing suppressor that functions to evade the antiviral silencing mechanism in plants, insect cells and mammalian cells (Bucher et al 2003;Hemmes et al 2007;Schnettler et al 2008Schnettler et al , 2009.…”
Section: Introductionmentioning
confidence: 99%